Sub-classification processes of the Cul-de-sac courtyards / Anniz Fazli Ibrahim Bajunid … [et al.] - Bajunid, Anniz Fazli Ibrahim; Abbas, Mohamed Yusoff; Nawawi, Abdul Hadi; Rameli, Alias (Universiti Teknologi MARA Cawangan Selangor, 2018)
Shah Alam has exhibited flourishing cul-de-sac courtyard neighbourhoods, which has stirred debatable interests. The objective of this paper is to continue the discourse in measurable analysis of subclassifications. The paper assembles physical data with key characteristics that make-up the physical construct of a cul-de-sac courtyard by administering measurements, observations and checklists. The sub-classification processes led to preliminary key factors such as density, size, design forms and user implications. 18 cul-de-sac courtyards in Shah were catalogued and inventoried, elucidating its syntax. The database introduced potential in longitudinal research of the socio-spatial micro-neighbourhood unit, towards pragmatic applications in emergent design practices.